Effectiveness Assay Of Ecoenzyme Based On Household Organic Waste On The Growth Of Fusarium Spp. In Vitro - Najla Lubis; Ruth Riah Ate Tarigan; Rico Kris Hadianata Tarigan; M. Ihlal Afiq (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The aim of this study is to find out how well eco-enzyme (EE), which is made from household waste, stops the pathogenic fungus Fusarium oxysporum from growing. An eco-enzyme is a fermentation solution produced from a mixture of organic waste, sugar, and water. In this study, various types of agricultural waste, such as fruit peels, vegetable waste, or other plants parts, were used US raw materials for making Eco-enzyme. The method used includes making EE with 2 types of raw material composition and various dilution concentrations of eco-enzyme dilution, namely 1: 0; 1: 10; 1:50; and 1: 100. Eco-enzyme testing was carried out in vitro on the growth of F. oxysporum mycelium. The results showed that Ecoenzyme from a mixture of fruit peel and vegetable waste had the highest inhibitory power against F. oxysporum at a dilution variation of 1: 100. This study concludes that ecoenzyme made from agricultural waste has the potential as a biological control agent against F. oxysporum. Using eco-enzymes can be an environmentally friendly solution for controlling plant diseases while reducing agriculture waste and overcoming environmental pollution.